DAMPAK MEDIA SOSIAL TERHADAP PRAKTIK MANAJEMEN DAN KETERLIBATAN KARYAWAN DI ERA DIGITAL - Neha Sartika; Muhammad Irwan Padli Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
In the digital era, social media has become an important element in management practices, especially in increasing employee engagement. With more than 170 million active users in Indonesia, platforms such as Facebook, Instagram, Twitter, and LinkedIn play a crucial role in the interaction between individuals and organizations. This study explores the impact of social media on employee engagement, collaboration, and innovation in the workplace. The research method used is a qualitative approach with literature analysis and documentation studies. The results show that social media not only accelerates internal communication, but also encourages better collaboration, increases creativity, and strengthens organizational culture. However, challenges such as the spread of inaccurate information and conflicts between employees need to be managed through clear policies and proper training. This study recommends strategies to utilize social media as a tool for career development and employee well-being, and provides guidance for organizations in creating a productive and innovative work environment.